2017
DOI: 10.14814/phy2.13207
|View full text |Cite
|
Sign up to set email alerts
|

Your mitochondria are what you eat: a high‐fat or a high‐sucrose diet eliminates metabolic flexibility in isolated mitochondria from rat skeletal muscle

Abstract: Extreme diets consisting of either high fat (HF) or high sucrose (HS) may lead to insulin resistance in skeletal muscle, often associated with mitochondrial dysfunction. However, it is not known if these diets alter normal interactions of pyruvate and fatty acid oxidation at the level of the mitochondria. Here, we report that rat muscle mitochondria does show the normal Randle‐type fat‐carbohydrate interaction seen in vivo. The mechanism behind this metabolic flexibility at the level of the isolated mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Decreased respiration observed after the addition of octanoylcarnitine and pyruvate is in line with previous studies that have reported that HFAT diets reduce the amount of PDH, in its active form (PDHa), and PDHa activity at rest, but not after a moderate CHO diet (21). Alterations in PDH activity have additionally been identified as a mechanism that underlies the regulation of metabolic flexibility in isolated rodent skeletal muscle mitochondria in response to altered substrate availability induced by high‐fat feeding (22). In addition, the reduction in respiration after 5 d of HFAT diet persisted after uncoupling (ETS CI + CII + ETF, and ETS CII), which suggests that the functional reductions in respiration occurred either at the level of CI/CII or downstream at CIII/ CIV, but not at complex V (ATP synthase).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased respiration observed after the addition of octanoylcarnitine and pyruvate is in line with previous studies that have reported that HFAT diets reduce the amount of PDH, in its active form (PDHa), and PDHa activity at rest, but not after a moderate CHO diet (21). Alterations in PDH activity have additionally been identified as a mechanism that underlies the regulation of metabolic flexibility in isolated rodent skeletal muscle mitochondria in response to altered substrate availability induced by high‐fat feeding (22). In addition, the reduction in respiration after 5 d of HFAT diet persisted after uncoupling (ETS CI + CII + ETF, and ETS CII), which suggests that the functional reductions in respiration occurred either at the level of CI/CII or downstream at CIII/ CIV, but not at complex V (ATP synthase).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates that 12 weeks of high‐fat or high‐sucrose feeding impairs mitochondrial function in glycolytic quadriceps muscles of rats (Jørgensen et al. ). In the present studies, SDH mRNA levels were increased after 2 and 4 weeks of HFS diet, suggesting a short‐term compensatory increase in oxidative capacity with metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin acts via the activation of peroxisome proliferator-activated receptors-alpha (PPAR-α) while leptin through direct activation of adenosine monophosphate-activated protein kinase (AMPK) [6]. Interestingly, isolated skeletal muscle mitochondria from rats fed high-sugar or high-fat diets showed reduced metabolic flexibility, indicating that substrate preference is independent of cytosolic-mitochondrial communication and in fact is a consequence of inherent mitochondrial biochemical network interactions [7]. Intriguingly, several food components, along with diet and exercise, have been indicated as a promising approach to manage the main clinical complications of metabolic syndrome [8], but their efficacy in modulating metabolic flexibility has been only partially investigated.…”
Section: Introductionmentioning
confidence: 99%